Strategi Corporate Social Responsibility (CSR) dalam Membangun Citra Perusahaan Pada PT. Crown Worldwide Indonesia - Azzahra Tsabitha (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This research is titled “Corporate Social Responsibility (CSR) Strategies in Building Company Image at PT. Crown Worldwide Indonesia” (Qualitative Study of Public Relations in carrying out CSR in a company). Image and reputation play a crucial role in communication for organizations, companies, and government institutions. PT. Crown Worldwide has implemented a Corporate Social Responsibility program aimed at enhancing its corporate image. The purpose of this thesis is to understand how PT. Crown Worldwide Indonesia improves its image through the implementation of Corporate Social Responsibility (CSR) programs. Another objective of this study is to assess the effectiveness of CSR programs in enhancing the company’s reputation. The author employed a qualitative descriptive and using RACE (Research, Action, Communication, & Evaluation) research approach, emphasizing in-depth investigation and utilizing image theory to gain insights into the effectiveness of CSR practices in terms of perception, cognition, motivation, and branding image related to PT. Crown Worldwide Indonesia. In addition, this study also uses Triple Bottom Line analysis to analyze PT. Crown Worldwide. The research findings indicate that the CSR program successfully builds a positive company image and serves as a communication function, making the company well-known among relevant communities and adding value to the organization itself.